Analyses of the First Professional Medical Undergraduate Regional Anatomy Written Short Answer Questions of Four Public Universities of Bangladesh (Journal of Rangpur Medical College, 2025)
Introduction: Anatomy has been a keystone subject of medical undergraduate curriculum for hundreds of years. A deep understanding of Anatomy is essential for all branches of medical science. Analysis of the assessment instrument is a good way of developing insight into what and how students are learning a particular subject. One valid way to do this must be an analysis of the question papers. Study of the question paper swould identify that how the different cognitive domains are addressed, how problem-based and other clinically-oriented knowledge of the student are assessed. Objective: To analyze the Regional Anatomy portion of the First Professional MBBS Anatomy written question papers of the last five years (January 2012 to November 2016) of the four public universities of Bangladesh for determining: the frequencies of ‘question-segment’s addressing the different levels of cognitive domains andthe frequencies of ‘problem-based’ and ‘other clinically-oriented’ ‘question-segment’s. Methods: The cross-sectional descriptive study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University, Dhaka during the period of March 2017 to February 2018. The study, all the ‘question-segment’s of Anatomy written question papers (only SAQ) dealing with Regional Anatomy of the First Professional MBBS Examination of the four public universities of Bangladesh of the last five years (January 2012 to November 2016) was targeted for analyzing. The frequencies of ‘question-segment’s those addressing different levels of cognitive domains(Remember, Understand, Apply, Analyze, Evaluate and Create level); ‘problem-based’ and ‘other clinically-oriented’ ‘question-segment’s were determined. Results: Most (89%) of ‘question-segment’s of the question of the question papers addressed the recall-level of the cognitive domain. 11% of ‘question-segment’ addressed the understand-level, but no ‘question-segments’ for addressing other levels of the cognitive domain could be identified. The frequency of ‘question-segment’s assessing the ‘other clinically-oriented’ question is 10.84%. No problem-based question-segments was identified. Conclusion: The result suggested that the higher levels of cognitive domains were neglected in the assessment-system and need to be addressed with appropriate weighting in the Anatomy written question papers.J Rang Med Col. 2025 Sep;10(2): 141-145